Teachers' Efforts in Developing Responsible Student Characters - hajariah, siti; Ayu, Sovia Mas; Hijriyah, Umi (Journal of Advanced Islamic Educational Management, 2022)
Responsibility is one of the mandates of the 2013 Curriculum for social attitude competencies. Learners who have responsibility will certainly complete their learning tasks seriously, which will affect their learning outcomes. Therefore, it is important to improve the responsibility of students at school. This study aims to determine the efforts of Islamic Religious Education teachers in improving the character and sense of responsibility of students at Ibnu Rusyd Islamic Elementary School in Kotabumi, North Lampung. The data obtained through interviews, observations, and documentation come from research data sources that are trusted and considered capable of answering the problems studied. The research data were analyzed in several stages, namely data reduction, data presentation, data verification, and drawing conclusions. The validity of the research data was tested by triangulating methods and triangulating sources. The results showed that teachers' efforts in fostering students' sense of responsibility were carried out through the involvement of school components. The nature of student responsibility, which includes responsibility for oneself, the environment, parents, and God, is formed through self-development and integrating responsibility character values in all subjects.